The Application of Microsampling Disks in Circular Dichroism Spectroscopy for Peptide and Nucleic Acid Drugs - Tsuji, Genichiro; Misawa, Takashi; Demizu, Yosuke (Chemical & pharmaceutical bulletin, 2024)
In recent years, there has been a growing focus on the development of medium-sized drugs based on peptides or nucleic acids owing to their potential therapeutic benefits. As some of these medium-sized drugs exert their therapeutic effects by adopting specific secondary structures, evaluating their conformational states is crucial to ensure the efficacy, quality, and safety of the drug products. It is important to assess the structural integrity of biomolecular therapeutics to guarantee their intended pharmacological activity and maintain the required standards for drug development and manufacturing. One widely utilized technique for quality evaluation is secondary structural analysis using circular dichroism (CD) spectroscopy. Given the higher production and quality control costs associated with medium-sized drugs compared with small-molecule drugs, developing analytical techniques that enable CD analysis with reduced sample volumes is highly desirable. Herein, we focused on a microsampling disk-type cell as a potential solution for reducing the required sample volume. We investigated whether CD spectral analysis using a microsampling disk could provide equivalent spectra compared with the standard cell (sample volume: approx. 300 µL). Our findings demonstrated that the microsampling disk (sample volume: 2–10 µL) could be successfully applied to CD spectral analysis of peptide and nucleic acid drugs, paving the way for more efficient and cost-effective quality evaluation processes.